New indices from microneurography to investigate the arterial baroreflex. Issue 12 (29th June 2017) - Laurin, Alexandre; Lloyd, Matthew G.; Hachiya, Tesshin; Saito, Mitsuru; Claydon, Victoria E.; Blaber, Andrew
Abstract: Baroreflex‐mediated changes in heart rate and vascular resistance in response to variations in blood pressure are critical to maintain homeostasis. We aimed to develop time domain analysis methods to complement existing cross‐spectral techniques in the investigation of the vascular resistance baroreflex response to orthostatic stress. A secondary goal was to apply these methods to distinguish between levels of orthostatic tolerance using baseline data. Eleven healthy, normotensive males participated in a graded lower body negative pressure protocol. Within individual neurogenic baroreflex cycles, the amount of muscle sympathetic nerve activity (MSNA), the diastolic pressure stimulus and response amplitudes, diastolic pressure to MSNA burst stimulus and response times, as well as the stimulus and response slopes between diastolic pressure and MSNA were computed. Coherence, gain, and frequency of highest coherence between systolic/diastolic arterial pressure (SAP/DAP) and RR‐interval time series were also computed. The number of MSNA bursts per low‐frequency cycle increased from 2.55 ± 0.68 at baseline to 5.44 ± 1.56 at −40 mmHg of LBNP. Stimulus time decreased (3.21 ± 1.48–1.46 ± 0.43 sec), as did response time (3.47 ± 0.86–2.37 ± 0.27 sec). At baseline, DAP‐RR coherence, DAP‐RR gain, and the time delay between decreases in DAP and MSNA bursts were higher in participants who experienced symptoms of presyncope. Results clarified the role of different branches of the baroreflex loop, and suggested functional adaptation of neuronal pathways to orthostatic stress. Abstract : Previous work indicates that sympathetically mediated vascular resistance responses are essential for maintenance of blood pressure by the baroreflex. We introduce new indices from microneurography that quantify the cause and effect of individual bursts of muscle sympathetic nerve activity, as well as measure the various time delays involved. These new indices clarified the role of different branches of the baroreflex loop, suggest functional adaptation of neuronal pathways to orthostatic stress, and highlighted differences between groups with different orthostatic tolerance using baseline data.